2022
DOI: 10.1183/16000617.0030-2022
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal carbon dioxide removal in acute hypoxaemic respiratory failure: a systematic review, Bayesian meta-analysis and trial sequential analysis

Abstract: Purpose:To assess the safety and efficacy of extracorporeal carbon dioxide removal (ECCO2R)versusstandard care in patients with acute hypoxaemic respiratory failure (AHRF).Methods:MEDLINE, Embase and clinical trial registries were searched from 1994 to 31 December 2021. We included randomised controlled trials (RCTs) and observational studies. Pairs of reviewers independently extracted data and assessed the risk of bias. The primary outcome was mortality. Secondary outcomes included ventilator-free days, lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Furthermore, there was no treatment effect on long-term respiratory function, posttraumatic stress disorder, cognitive dysfunction, or health-related quality of life (11). Although experience to date suggests that low-flow ECCO 2 R is both feasible and capable of supporting reductions in Vt and driving pressure in moderate ARDS (12), the benefits of doing so have not been established. A recent systematic review and Bayesian meta-analysis of 21 studies (including 3 randomized controlled trials [RCTs]) in AHRF revealed a posterior probability of 73% for increased mortality with the use of ECCO 2 R (12).…”
mentioning
confidence: 99%
“…Furthermore, there was no treatment effect on long-term respiratory function, posttraumatic stress disorder, cognitive dysfunction, or health-related quality of life (11). Although experience to date suggests that low-flow ECCO 2 R is both feasible and capable of supporting reductions in Vt and driving pressure in moderate ARDS (12), the benefits of doing so have not been established. A recent systematic review and Bayesian meta-analysis of 21 studies (including 3 randomized controlled trials [RCTs]) in AHRF revealed a posterior probability of 73% for increased mortality with the use of ECCO 2 R (12).…”
mentioning
confidence: 99%